Deconversion Processes in Adolescence: the Role of Parental and Peer Factors - Łysiak, Małgorzata (Religions, 2020)
The phenomenon of abandonment of faith, which in psychology is referred to as deconversion, is observed today. Deconversion is particularly widespread in young people. In this paper we examine the parents’ religiosity, parents’ care, and social support as potential predictors of deconversion in adolescents. Specifically, we aimed to analyse whether or not parents’ religiousness, individual differences in childrens’ attachment to their parents, and received support from family, friends, and significant others differentiate adolescents in deconversion processes. The hypotheses were tested on a sample of 232 adolescents in a cross-sectional study, which applied three scales. The Adolescent Deconversion Scale, Parental Bonding Instrument, and Multidimensional Scale of Perceived Social Support. The results showed that adolescents having both caring and religious parents are less prone to abandon faith and to moral criticism than those having caring but not religious parents or those having religious but not caring parents. The low social support group was more likely to abandon faith and moral criticism than moderate or high social support groups. Regression analyses revealed that deconversion in adolescence is negatively predicted by the mother’s care and friends’ support.